DESIGN OF A WEB-BASED MARKETPLACE AS A MEANS OF SELLING AND PURCHASING EVENT TICKETS IN THE CIAYUMAJAKUNING REGION - Dhiyaul Haq , Adly Muhamad; Bhakti , M.Herdian; Susanto, Budi (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2025)
Marketplace is a place that connects sellers and buyers to conduct buying and selling transactions. The purpose of designing and building a web-based marketplace platform that facilitates the sale and purchase of event tickets in the Ciayumajakuning region. The Ciayumajakuning region currently does not have a means of selling and purchasing event tickets so that the lack of information about events that are currently being held in the Ciayumajakuning region. To sell event tickets currently still using manual methods by meeting directly with buyers and promotions through social media so that it is less than optimal in selling tickets. This sometimes causes many problems including the circulation of fake event tickets. The application created is a web-based marketplace as a means of selling and purchasing event tickets for ciayumajakuning area events. The website was created using the Nattive PHP programming language, the application interface was developed from the Bootstrap CSS Framework and as a database is MySQL. The method used is RAD (Rapid Application Development). This web-based application can present information about events that may be currently ongoing or upcoming. This application allows users to view a list of events with detailed information such as date, time, location, category, and event description. Keywords: Marketplace, Website, Sales, Purchase, Event tickets.